The era of crowds: Gustave Le Bon, crowd psychology, and conceptualizations of mass-elite relations in China - Ohlberg, Mareike (The dynamics of transculturality, 2015)
This paper analyzes the reception and appropriation of Gustave Le Bon’s Psychologie des foules (English title: The Crowd: A Study of the Popular Mind) in China from the early twentieth century to this day. Written in 1895 and intended as a guide for statesmen on how to deal with crowds during an age in which their rising political influence was viewed with fear by many, the work enjoyed several waves of popularity in China--most recently in the early twenty-first century--and was used by different groups for very different purposes. The paper will focus on the different translations, the routes and intermediaries through which the work came to China, and the purposes for which it was appropriated. It finds that political elites have tried to use ideas found in Psychologie des foules both to mobilize and to contain the Chinese people. Moreover, the findings of the study suggest that when studying cultural flows from one context to another, the definition of culture should be explicitly expanded to accommodate flows across time and space as well as between different ideologies, academic disciplines, or any other parameter that erects borders between different groups of people.
First Online: 10 October 2014
Gesehen am 02.06.2020